2016
DOI: 10.1016/j.neuropharm.2016.09.013
|View full text |Cite
|
Sign up to set email alerts
|

Altered nocifensive behavior in animal models of autism spectrum disorder: The role of the nicotinic cholinergic system

Abstract: Caretakers and clinicians alike have long recognized that individuals with autism spectrum disorder (ASD) can have altered sensory processing, which can contribute to its core symptoms. However, the pathobiology of sensory alterations in ASD is poorly understood. Here we examined nocifensive behavior in ASD mouse models, the BTBR T+Itpr3tf/J (BTBR) and the fragile-X mental retardation-1 knockout (Fmr1-KO) mice. We also examined the effects of nicotine on nocifensive behavior given that nicotine, a nicotinic ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 78 publications
3
24
0
3
Order By: Relevance
“…Similarly, with recent study reported that chronic nicotine in drinking water did not affect overall locomotion in male mice [Calarco et al, 2017], but female C57BL/6J; however, at a similar dose of nicotine in another past study showed that both male and female C57BL/6J mice increased in LA and only males showed locomotor activation at a lower dose of nicotine (100 μg/mL), but female mice were less sensitive to locomotor activation even though nicotine intake was actually higher in females than males, but plasma levels of cotinine were equivalent for both sexes [Caldarone et al, 2008]. In contrast, Wang et al [2016] reported that chronic oral nicotine at 200 and 400 μg/mL, but not 100 μg/mL, decreased overall physical activity of BTBR mice in the open-field test. Previous experiments reported that female rats had more locomotor sensitivity in response to chronic nicotine [Booze et al, 1999;Faraday, O'Donoghue, & Grunberg, 2003;Harrod et al, 2004;Kanýt, Stolerman, Chandler, Saigusa, & Pö gün, 1999], indicating sex and strain differences in behavioral locomotor response to nicotine treatment.…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations
“…Similarly, with recent study reported that chronic nicotine in drinking water did not affect overall locomotion in male mice [Calarco et al, 2017], but female C57BL/6J; however, at a similar dose of nicotine in another past study showed that both male and female C57BL/6J mice increased in LA and only males showed locomotor activation at a lower dose of nicotine (100 μg/mL), but female mice were less sensitive to locomotor activation even though nicotine intake was actually higher in females than males, but plasma levels of cotinine were equivalent for both sexes [Caldarone et al, 2008]. In contrast, Wang et al [2016] reported that chronic oral nicotine at 200 and 400 μg/mL, but not 100 μg/mL, decreased overall physical activity of BTBR mice in the open-field test. Previous experiments reported that female rats had more locomotor sensitivity in response to chronic nicotine [Booze et al, 1999;Faraday, O'Donoghue, & Grunberg, 2003;Harrod et al, 2004;Kanýt, Stolerman, Chandler, Saigusa, & Pö gün, 1999], indicating sex and strain differences in behavioral locomotor response to nicotine treatment.…”
Section: Discussionmentioning
confidence: 81%
“…The doses of nicotine used in our study (50, 100, and 400 mcg/mL) were selected based on our previous studies and others in the literature [AlSharari et al, 2013;Grabus et al, 2005;Mesa-Gresa, Perez-Martinez, & Redolat, 2013;Caruso et al, 2018;Kamens et al, 2015;Klein, Stine, Vandenbergh, Whetzel, & Kamens, 2004;Wang et al, 2015;Wang et al, 2016] that have shown to increase plasma concentrations of nicotine and cotinine and to increase nicotine binding to high-affinity nAChRs in the brains of C57BL/6J mice [Caldarone, King, & Picciotto, 2008;King, Caldarone, & Picciotto, 2004;Sparks & Pauly, 1999;Calarco, Lee, & Picciotto, 2017]. Earlier studies have shown that nicotine can be administered chronically for several weeks in the drinking water to mice in a way that plasma nicotine pharmacokinetics and cotinine concentration mimic or similar to and above those reported in smokers of human smokers [Nordberg et al, 1985;Pekonen, Karlsson, Laakso, & Ahtee, 1993;Pietila, Laakso, & Ahtee, 1995;Klein et al, 2004;Grabus et al, 2005;Caldarone et al, 2008;Salas and De Biasi, 2008;Wang et al, 2015;Wang et al, 2016]. Chronic nicotine exposure is known to cause an increase in the density of neuronal nicotinic receptor subtypes and upregulates some nAChRs within the CNS [Marks, Burch, & Collins, 1983;Schwartz & Kellar, 1983;Schwartz & Kellar, 1985;Ksir, Hakan, Hall, & Kellar, 1985;Wonnacott, 1990;Pauly, Marks, Gross, & Collins, 1991;Pauly, Marks, Robinson, van de Kamp, & Collins, 1996;Sanderson et al, 1993;Trauth, Seidler, McCook, & Slotkin, 1999;…”
Section: Drugsmentioning
confidence: 99%
See 2 more Smart Citations
“…While the biological bases of ASD are only partially understood, a wide range of experimental and clinical observations suggest that cholinergic system alterations could be involved in these disorders [2][3][4][5][6][7]. That is why some authors have proposed that the nicotinic cholinergic system might be involved in the pathogenesis of ASD [8]. Pathologic studies have indeed highlighted that nicotinic acetylcholine receptor subtypes are altered in brain of autistic individuals.…”
Section: Autismmentioning
confidence: 99%